O Bobo, by Herculano, and its models Ivanhoe and Notre Dame de Paris: The Portuguese version of the nation formation - Pavanelo, Luciene Marie [UNESP] (Universidade Estadual de Maringa, 2019)
The article proposes an analysis of the novel O Bobo, by Alexandre Herculano, in comparison with Ivanhoe, by Walter Scott, and Notre Dame de Paris by Victor Hugo. Although some critics have already done a comparative reading of the works of these writers, they usually focus on the study of sources and influences, trying to associate Herculano to Romanticism. We propose, in this study, a comparative reading divergent from the usual ones as defended by Santiago (2000) and Carvalhal (2006), seeking to understand the historical specificities of these authors, and going beyond the limited categories of literary schools. It is intended, with this study, to propose a new look on the work of Herculano, mainly in the way he portrayed the past in O Bobo, differently from Scott and Hugo. It is concluded that the difference in this portrait of the past is directly related to the way in which these writers perceive not only the past of their country but also their present.
O Bobo de Herculano e seus modelos Ivanhoé e Notre Dame de Paris: A versão Portuguesa da formação da Nação
Keywords: century th century.; Comparative literature; Portuguese literature